A new genus of Textricini Lehtinen, 1967 (Araneae, Agelenidae) from Anatolia - Kaya Rahşen S.; Zamani Alireza; Yağmur Ersen Aydın; Marusik Yuri M. (Pensoft Publishers, 2025)
Türkiye is known to have the highest diversity of the spider family Agelenidae in the Western Palaearctic and the highest diversity of the subfamily Ageleninae globally. The new agelenid genus Anatextrix gen. nov. (Ageleninae, Textricini) and its type species, A. spectabilis sp. nov. (♂♀; Mersin and Adana provinces, southern Türkiye), are described. A key to all four genera of Textricini is provided.